PEMERIKSAAN GLUKOSA DARAH DAN COMPLETE BLOOD COUNT SEBAGAI LANGKAH PENCEGAHAN KOMPLIKASI HIPERGLIKEMIA PADA PARA PEMANGKU - Wande, I.N.; Dewi, D.A.P.R.; Santhi, D.G.D.D.; Santika, I.K.A.; Linawati, N.M. (Buletin Udayana Mengabdi; Vol 23 No 3 (2024): Buletin Udayana Mengabdi, 2023)
The priest (Pemangku) is in charge of accompanying the yadnya ceremony and is generally elderly with various status of health conditions they have. The aim of this program is to conduct early detection of hyperglycemia and complications of anemia through blood glucose checks and complete blood counts for the priest in Ketewel Village free of charge. This program is carried out by checking blood glucose with a glucose Point of Care Testing (POCT) and checking a complete blood count with a Sysmex? XP100. The priest in Ketewel Village were gathered at the Wantilan Hall in Ketewel Village, routine physical examinations were carried out, blood glucose was checked and 2 ml of venous blood was taken into the K3EDTA tube for complete blood count examination at the Mantra Medika Clinical Laboratory. A total of 68 the priest attended as participants in the Udayana Serving Program. The average age of male the priest is 57.35 ± 11.11 years old and that of female the priest is 57.78 ± 8.14 years old. Laboratory examination results showed the average fasting blood glucose level for male the priest (124.5±31.3 mg/dl) and female the priest (110.2±20.3 mg/dl) which did not include the criteria for diabetes mellitus. Examination of the complete blood count in the form of hemoglobin, erythrocytes, hematocrit, leukocytes and platelets also showed results within the normal range of values (hemoglobin= 12-16 g/dl, erythrocytes = 4-5,2 x10^6 /ul, leukocytes = 4,1-11 x10^3 /ul, platelets = 140-440 x10^3 /ul). The priest are also given supplements in the form of vitamins and fresh milk. Keywords : complete blood count, blood glucose, the priest (Pemangku).   Pemangku Pura bertugas untuk nganteb atau mengiringi upacara yadnya dan umumnya lanjut usia  dengan berbagai status kondisi kesehatan yang dimiliki. Tujuan dari program pengabdian ini yaitu untuk melakukan deteksi dini hiperglikemia dan komplikasi terjadinya anemia melalui pemeriksaan gratis glukosa darah dan complete blood count pada para Pemangku yang ada di Desa ketewel. Pengabdian ini dilakukan dengan cara melakukan pemeriksaan gratis glukosa darah dengan alat P oint of C are T esting (POCT) glukosa dan pemeriksaan complete blood count dengan alat S ysmex Ò XP100. Pemangku yang ada di Desa Ketewel dikumpulkan di Balai Wantilan Desa Ketewel, dilakukan pemeriksaan fisik rutin, pemeriksaan glukosa darah dan pengambilan darah vena sebanyak 2 ml yang dimasukkan ke tabung K3EDTA untuk pemeriksaan complete blood count di Laboratorium Klinik Mantra Medika. Sebanyak 68 Pemangku hadir sebagai peserta dalam program Udayana Mengabdi. Rerata usia Pemangku laki-laki yaitu 57,35 ± 11,11 tahun dan Pemangku wanita yaitu 57,78 ±8,14 tahun. Hasil pemeriksaan laboratorium menunjukkan rerata kadar glukosa darah puasa Pemangku laki-laki (124,5±31,3 mg/dl) dan Pemangku wanita (110,2 ± 20,3 mg/dl) yang menunjukkan belum termasuk kriteria diabetes melitus. Pemeriksaan complete blood count berupa hemoglobin, eritrosit, hematokrit, leukosit dan trombosit juga menunjukkan hasil dalam rentang nilai normal. Para pemangku juga diberikan suplemen berupa vitamin dan susu cair.